Application of Automated Throw Backstripping Method to Characterize Recent Faulting Activity Migration in the Al Hoceima Bay (Northeast Morocco): Geodynamic Implications - Tendero-Salmerón, Víctor; Lafosse, Manfred; d’Acremont, Elia; Rabaute, Alain; Azzouz, Omar; Ercilla, Gemma; Makkaoui, Mohamed; Galindo-Zaldivar, Jesus (Frontiers in Earth Science, 2021)
Automation of the throw backstripping method has proven to be an effective tool for the determination of the evolution of tectonic activity in wide fault zones. This method has been applied to the Al Hoceima Bay (southwesternmost Mediterranean, Alboran Sea) for a time period covering the last 280 kyr on 672 faults imaged on 265 high-resolution seismic reflection profiles. This area was affected by major earthquakes and corresponds to a transtensional basin deformed by growth faults. The automated application of throw backstripping allowed for a faster deciphering of the migration of tectonic activity. Results show a westward migration of the deformation with quickly increasing deformation rates in the most recent time frames near the Al Hoceima City, the most populated area. This migration is in agreement with the current seismicity, the GPS data and recent brittle deformation data. Vertical throw rates of up to 0.47 mm/yr have been calculated, for the most recent time periods, in segments of the Bokkoya fault zone. The westward migration of the deformation fits with the reconstruction suggested by westernmost Mediterranean geodynamic models during the Pleistocene, and it may be the consequence of interaction between the NW movement of the South Alboran indenter and the back Rif south-westwards displacement. The highly accurate constraints of evolution of tectonic activity offered by this automation will substantially improve the seismic hazard assessment.